The Semantic Features on English Synonymous Nouns of “Idea” - Saraswati Rachmadewi, Maretha (Humanis; Vol 22 No 3 (2018), 2018)
This study is aimed to see the use of distribution of the English synonymous noun “Idea”, finding the meanings of each word as well as explaining the semantic features in each synonymous word. The English synonymous nouns “Idea” are belief, notion, opinion, plan, and thought. The related data were collected from COCA using Corpus method with a concordance technique. Meanwhile, qualitative and quantitative method was used to analyze the data. The result of the analysis shows that Idea is most frequently used, then followed by plan, thought, opinion, belief, and notion. In terms of the semantic features, there are ten features on content; they are: suggestion, strong feeling, confidence/trust, assumption, impression, not a fact, judgment, detail, arrangement, and politics. In the circumstance point of view, there are three features, they are formal, common, and suddenly. Furthermore, in the reason there are 4 features, which are something/someone that has been highly trusted, uncertain and there are many options, something without doubt and well planned, and need a clear or scientific explanation.